1984
DOI: 10.2136/sssaj1984.03615995004800060020x
|View full text |Cite
|
Sign up to set email alerts
|

A Soil Test for Nitrogen Availability to Corn

Abstract: A soil test for N availability to corn (Zea mays L.), NO‐3‐ to 30cm when plants are 15 to 30 cm tall, was evaluated on a wide range of soils at 33 locations in Vermont and one in New York state. The NO‐3‐N present at the time of sampling is a result of an integration of all the soil and weather factors that have influenced the availability of N prior to the time for sidedress fertilizer application. There was a typical response relationship between soil test NO‐3‐N and corn silage yield on plots that only rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
193
2
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(209 citation statements)
references
References 0 publications
10
193
2
4
Order By: Relevance
“…3). Close relationships between soil NO 3 -in spring and the response to N fertilizers of crops have been reported in many studies (Magdoff et al 1984;Dahnke and Johnson 1990;Holford et al 1997). Other studies, however, found that this approach is not satisfactory under cool and humid environments (Neeteson 1995;Bélanger et al 1998;Bittman and Kowalenko 1998).…”
Section: Economically Optimum N Fertilizer Ratementioning
confidence: 54%
See 1 more Smart Citation
“…3). Close relationships between soil NO 3 -in spring and the response to N fertilizers of crops have been reported in many studies (Magdoff et al 1984;Dahnke and Johnson 1990;Holford et al 1997). Other studies, however, found that this approach is not satisfactory under cool and humid environments (Neeteson 1995;Bélanger et al 1998;Bittman and Kowalenko 1998).…”
Section: Economically Optimum N Fertilizer Ratementioning
confidence: 54%
“…The pre-seeding and the pre-sidedress soil N tests have long been recommended as methods of assessing N availability and predicting fertilizer N requirements for different crops, especially for corn (Zea mays L.) in sub-humid areas in the United States of America and Canada (Magdoff et al 1984;Hergert 1986;Zebarth and Paul 1997). In Québec, the use of a soil NO 3 -test is still limited and only a few studies have been carried out on corn and wheat (Giroux et al 1993).…”
mentioning
confidence: 99%
“…The poor relationship between Nop and spring soil NO 3 -N content agrees with results on spring wheat grown in the same vicinity (Bélanger et al 1998). Stronger correlations reported in studies from other parts of the world and other crops (Magdoff et al 1984;Holford et al 1997) may be explained by climatic conditions. Indeed, spring pre-plant soil NO 3 -N measurements are deemed to be unreliable indices of N fertilizer requirements under cool-humid environments (Neeteson 1995).…”
Section: Soil No 3 -N Contents In Spring and Mid-seasonmentioning
confidence: 82%
“…With the linear-plus-plateau model, Zebarth and Paul (1997) report a critical value of about 33 mg NO 3 -N kg -1 soil for silage corn produced in British Columbia. The Cate-Nelson method, used by Magdoff et al (1984), indicates a greater probability of response of corn to N fertilizer when soil NO 3 -N was less than 16 mg NO 3 -N kg -1 soil. Soil sampling on the potato hills relatively close to where N was applied may explain the relatively large NO 3 -N contents observed in our study.…”
Section: Mid-season Soil No 3 -N Content Andmentioning
confidence: 99%
“…Nitrogen applications at sidedress should be based on pre-sidedress soil or plant tests as indicators of soil available N. The pre-sidedress soil nitrate test became well known after the work of Magdoff et al (1984). Thereafter, many researchers included this soil N availability index in their studies.…”
Section: Introductionmentioning
confidence: 99%